Longitudinal Survey of COVID-19 Burden and Related Policies in U.S. Neonatal Intensive Care Units - Ahmad, Kaashif A.; Darcy-Mahoney, Ashley; Kelleher, Amy S.; Ellsbury, Dan L.; Tolia, Veeral N.; Clark, Reese H. (American Journal of Perinatology, 2020)
Objective This study aimed to determine the prevalence of confirmed novel coronavirus disease 2019 (COVID-19) disease or infants under investigation among a cohort of U.S. neonatal intensive care units (NICUs). Secondarily, to evaluate hospital policies regarding maternal COVID-19 screening and related to those infants born to mothers under investigation or confirmed to have COVID-19.Study Design Serial cross-sectional surveys of MEDNAX-affiliated NICUs from March 26 to April 3, April 8 to April 19, May 4 to May 22, and July 13 to August 2, 2020. The surveys included questions regarding COVID-19 patient burden and policies regarding infant separation, feeding practices, and universal maternal screening.Results Among 386 MEDNAX-affiliated NICUs, responses were received from 153 (42%), 160 (44%), 165 (45%), 148 (38%) across four rounds representing an active patient census of 3,465, 3,486, 3,452, and 3,442 NICU admitted patients on the day of survey completion. Confirmed COVID-19 disease in NICU admitted infants was rare, with the prevalence rising from 0.03 (1 patient) to 0.44% (15 patients) across the four survey rounds, while the prevalence of patients under investigation increased from 0.8 to 2.6%. Hospitals isolating infants from COVID-19-positive mothers fell from 46 to 20% between the second and fourth surveys, while centers permitting direct maternal breastfeeding increased 17 to 47% over the same period. Centers reporting universal severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) screening for all expectant mothers increased from 52 to 69%.Conclusion Among a large cohort of NICU infants, the prevalence of infants under investigation or with confirmed neonatal COVID-19 disease was low. Policies regarding universal maternal screening for SARS-CoV-2, infant isolation from positive mothers, and direct maternal breastfeeding for infants born to positive mothers are rapidly evolving. As universal maternal screening for SARS-CoV-2 becomes more common, the impact of these policies requires further investigation.Key Points
Keywords: COVID-19; NICU; breastfeeding; survey